Disruption of FOXF2 as a Likely Cause of Absent Uvula in an Egyptian Family. (June 2019) - Seselgyte, R.; Bryant, D.; Demetriou, C.; Ishida, M.; Peskett, E.; Moreno, N.; Morrogh, D.; Sell, D.; Lees, M.; Farrall, M.; Moore, G.E.; Sommerlad, B.; et al.
This study investigated the genetic basis of an unusual autosomal dominant phenotype characterized by familial absent uvula, with a short posterior border of the soft palate, abnormal tonsillar pillars, and velopharyngeal insufficiency. Cytogenetic analysis and single-nucleotide polymorphism–based linkage analysis were investigated in a 4-generation family with 8 affected individuals. Whole exome sequencing data were overlaid, and segregation analysis identified a single missense variant, p.Q433P in the FOXF2 transcription factor, that fully segregated with the phenotype. This was found to be in linkage disequilibrium with a small 6p25.3 tandem duplication affecting FOXC1 and GMDS . Notably, the copy number imbalances of this region are commonly associated with pathologies that are not present in this family. Bioinformatic predictions with luciferase reporter studies of the FOXF2 missense variant indicated a negative impact, affecting both protein stability and transcriptional activation. Foxf 2 is expressed in the posterior mouse palate, and knockout animals develop an overt cleft palate. Since mice naturally lack the structural equivalent of the uvula, we demonstrated FOXF2 expression in the developing human uvula. Decipher also records 2 individuals with hypoplastic or bifid uvulae with copy number variants affecting FOXF2 . Nevertheless, given cosegregation with the 6p25.3 duplications, we cannot rule out a combined effect of these gains and the missense variant on FOXF2 function, which may account for the rare palate phenotype observed.